2004
DOI: 10.1046/j.1365-2761.2003.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute columnaris infection in channel catfish, Ictalurus punctatus (Rafinesque): efficacy of practical treatments for warmwater aquaculture ponds

Abstract: Columnaris disease was induced in channel catfish, Ictalurus punctatus (Rafinesque), by bath exposure to four highly virulent isolates of Flavobacterium columnare. In untreated controls, mortality began 20 h after exposure and reached 100% by 48 h. Mortality in channel catfish given antibiotic treatments with oxytetracycline or a combination of sulphadimethoxine and ormetoprim in feed prior to bacterial challenge was zero with all four strains of F. columnare. Diquat (Zeneca Agricultural Products, Wilmington, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 10 publications
3
70
0
3
Order By: Relevance
“…Chloramine-T, potassium permanganate, benzalkonium chloride, hydrogen peroxide and copper sulphate have all been tested experimentally and shown to be effective (Jee & Plumb 1981, Wakabayashi 1991, Speare & Arsenault 1997, Altinok 2004. In a study by Thomas-Jinu & Goodwin (2004), Diquat ® (herbicide) was shown to be very effective against columnaris disease, and no fish mortality occurred after challenge with F. columnare. However, the chemicals mentioned above can be harmful to the fish and the user (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chloramine-T, potassium permanganate, benzalkonium chloride, hydrogen peroxide and copper sulphate have all been tested experimentally and shown to be effective (Jee & Plumb 1981, Wakabayashi 1991, Speare & Arsenault 1997, Altinok 2004. In a study by Thomas-Jinu & Goodwin (2004), Diquat ® (herbicide) was shown to be very effective against columnaris disease, and no fish mortality occurred after challenge with F. columnare. However, the chemicals mentioned above can be harmful to the fish and the user (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial diseases of freshwater fish epithelia have been extensively studied with the primary focus upon bacteria from the Cytophagales, such as bacterial gill disease caused by Flavobacterium branchiophilum (Ostland et al 1994(Ostland et al , 1995, and necrotizing skin diseases such as columnaris disease caused by F. columnare (Thomas-Jinu & Goodwin 2004) and bacterial cold-water disease caused by F. psychrophilum (Cipriano et al 1996 and review by Nematollahi et al 2003). However, in marine fishes relatively few bacterial skin and gill diseases have been characterised.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation that has prevented a more comprehensive understanding of columnaris disease in channel catfish (Ictalurus punctatus) has been the lack of a standardized immersion F. columnare infectivity model, which has made comparison of findings among laboratories difficult. Immersion infectivity models with F. columnare and channel catfish have routinely required disrupting the integrity of skin through abrasion or have led to uncharacteristic acute or large-scale mortality of test animals (Altinok and Grizzle, 2001;Bader et al, 2003;Thomas-Jinu and Goodwin, 2004;Bader et al, 2006;Soto et al, 2008;Darwish et al, 2008).…”
Section: Introductionmentioning
confidence: 99%